Contribution in mathematical methodologies that improve the quality and compression of advanced video - Bokun, Jorge Robles (2019)
The main objective is to transmit HD content enhanced with high image quality throughstreaming video.In recent years the technological advance, in what refers to the transmission of highresolution video with high resolution, is booming but showing a low quality of video ina series of frames per second using more bandwidth and at the same time less often.Thismeans greater loss of information per data sent, and giving priority to moving objects and3D images but forgetting the quality and fidelity of it. This need motivated me to developthis research to find an equitable and progressive solution to the low quality of video, butbased on the analysis of the standards that gave rise to the compression. As this study ledme to contribute or modify the mathematical algorithms within the compression standardsalready known as: MPEG-1, MPEG-2, MPEG-4, H.264 and H.265, with an exhaustive researchusing graphs, diagrams and schemes that justify the results obtained, as well as performancesimulations through the use of scientific computer software.